Digital Competencies of Managers and Lawyers: Their Significance and Prospects in the Current Context - Fedorchuk, Olha; Sukhovirskyi, Oleh (Pedagogical Discourse, 2024)
The article deals with the study of the effectiveness of managers and lawyers in the context of rapid digital transformation of society. The theoretical and methodological aspects of the concept of «professional effectiveness» are analyzed, which is considered in the context of modern requirements for professional competence. Particular attention is paid to the relationship between the concepts of «competence» and «competency”, where the former is defined as the potential for learning, and the latter as the result of acquiring knowledge and skills. Various approaches to defining professional competence are explored. In particular, the importance of professional identity, ethics, competitiveness, the desire for scientific improvement, and motivation for continuing education are emphasized. The authors emphasize that in the post-industrial stage of societal development, there is a transition from qualification assessment to competence assessment, which reflects a change in the requirements for professionalism. A key aspect of the research is the impact of digital technologies on the formation of professional competencies of managers and lawyers. The authors note that digital skills are becoming an integral part of professional activity, and intensive technological progress creates new digital needs and competencies. Considering legal education as an environment for the formation of a new generation of lawyers, the authors emphasize the need to take into account the processes of digitalization in the educational process. Digital competencies of a lawyer are considered as a basic set of knowledge, abilities, and skills necessary for successful professional activity in the modern world. The manifestations of the combination of competencies of a lawyer and a manager, especially in the context of small business, where there is often a need for universal specialists with both legal and managerial knowledge, are analyzed. Digital skills of managers as an important condition for the development of the future economy are also considered. Key aspects of IT training, such as digital literacy, cybersecurity, creativity, adaptability, communication, and emotional intelligence, are highlighted. Significant attention in the article is paid to the impact of digitalization on the legal field, in particular the automation of routine tasks and the virtualization of legal services. Various interpretations of the concept of digitalization of jurisprudence are presented. At the same time, the authors warn against the potential negative consequences of excessive automation, such as the devaluation of the human component in the profession and the decrease in public trust in law. The need to maintain a balance between technological and human factors in legal activity is emphasized. The inevitability and generally positive impact of digitalization on the professional activity of managers and lawyers are emphasized, but the importance of maintaining personal approach and avoiding complete robotization is also stressed. The authors argue that digital competence is a condition for professional success and includes information and media literacy, communication and collaboration, digital content creation, digital security, problem-solving, and continuous self-improvement.